Rancang Bangun Sistem Antrian Online Menggunakan Metode Single Channel-Multi Phase Studi Pada Dinas Sosial Kabupaten Labuhanbatu - Sirait, Roby Gusmawan; Harahap, Syaiful Zuhri; Ritonga, Irmayanti (Jurnal Informatika, 2024)
Labuhanbatu District Social Office is an institution implementing social affairs of government under and responsible to the head of the region (Regent).  In this case the Labuhanbatu District Social Service Office applies many arrangements in between what happens. The way that is done is very manual, namely by setting the queue NumberOne by one. With a very small limit on the number of passengers, this causes queues to accumulate, coupled with situations that affect his daily life. In the process of service that is done, there is a way of service that must be done because a lot of attention should be paid to the way the service is done now is not very effective. So it is necessary to create a simulation of community service system that can identify community services in the Office of Social Services Labuhanbatu District. During the service takes place the time needed between one another in getting the service to be efficient first came to be served in the service. The reason for the research using this topic is that research on the topic is still not done in the Labuhanbatu District Social Service with Inter-system using Single Channel-Multi Phase method.  So that the Social Service of Labuhanbatu Regency can serve the community to the maximum and the community feels comfortable and fair.